Two dung beetle species that disperse mimetic seeds both feed on eland dung - Midgley, Jeremy J.; White, Joseph D.M. (South African Journal of Science, 2016)
Scarabaeus spretus zur Strassen was observed to roll and bury Ceratocaryum argenteum (Restionaceae) seeds in the sandplain fynbos of the Potberg area of the De Hoop Nature Reserve, South Africa. This species is the second dung beetle species found to be deceived by the faecal mimicry of C. argenteum seeds – the first species being Epirinus flagellatus. An isotopic analysis suggests that both these dung beetle species most likely feed on eland (Taurotragus oryx), not bontebok (Damaliscus pygargus pygargus), dung. Thus the model in this mimicry is eland dung; this interaction suggests large herbivores are an integral part of this fynbos. Supplementary Video: A Scarabaeus spretus dung beetle burying seeds of Ceratocaryum argenteum: https://youtu.be/C_VFlAcsx10